2015
DOI: 10.1177/1932296815599551
|View full text |Cite
|
Sign up to set email alerts
|

Economic Value of Improved Accuracy for Self-Monitoring of Blood Glucose Devices for Type 1 Diabetes in Canada

Abstract: Glucose monitoring, frequent hemoglobin A1c testing (HbA1c), and intensive insulin treatment are of critical importance for managing type 1 diabetes. 1 Patient self-monitoring of blood glucose (SMBG) requires daily tracking of glucose concentrations, and should be carried out multiple times per day for patients using intensive insulin therapy. Frequent SMBG improves glycemic control and assists in avoiding acute complications such as hypoglycemia. 1,2 However, not all SMBG devices have the same accuracy which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Our modeling findings are similar to other modeling results associating SMBG accuracy standards with clinical and economic outcomes. 10,45 Our previous modeling findings found improved accuracy of SMBG devices in type 1 diabetes resulted in efficient and affordable findings from a Canadian payer perspective. Our current analysis differs with the addition of insulin-treated type 2 diabetes patients and the application to an English NHS perspective which has a different willingness-to-pay threshold than Canada.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Our modeling findings are similar to other modeling results associating SMBG accuracy standards with clinical and economic outcomes. 10,45 Our previous modeling findings found improved accuracy of SMBG devices in type 1 diabetes resulted in efficient and affordable findings from a Canadian payer perspective. Our current analysis differs with the addition of insulin-treated type 2 diabetes patients and the application to an English NHS perspective which has a different willingness-to-pay threshold than Canada.…”
Section: Discussionmentioning
confidence: 97%
“…This approach is consistent with the previous version of this model used in the Canadian setting which adopted equivalent utility values for the two health states. 10 For type 2 diabetes, the economic model informing the NICE Guideline 30 was based on the same UKPDS model and used the same health states as the current model.…”
Section: Utility Inputsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average follow-up time was 1.4 years: if the study had measured HbA 1c change over one year, the observed change would be approximately 0.11% (0.16/1.4). It is possible that such small changes accumulating over a longer time period could be clinically important, impacting on quality of life or the risk of long-term diabetes complications, as discussed by McQueen et al[ 31 ]. This issue calls for further research to investigate the long-term effects.…”
Section: Discussionmentioning
confidence: 99%